Beyond Elder Law New Directions in Law and Aging - Doron, Israel; Soden, Ann M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
All over the world, there is a growing interest in the relationship between law and aging: How does the law influence the lives of older people? Can rights, advocacy and representation advance the social position of the aged and combat ageism? What are the new and cutting-edge frontiers in the field of elder law? Should there be a new international human rights convention in this field? These are only a few of the many questions that arise. This book attempts to answer some of these questions and to set the agenda for the future development of elder law across the globe. Taking into account existing research and knowledge, leading scholars from different continents (North America, Europe, Asia, and Australia) present in this book original and novel ideas regarding the future development of elder law. These ideas touch upon key topics such as elder guardianship, citizenship, mental capacity, elder abuse, human rights and international law, family relationships, age discrimination, and the right to die. This book can thus serve as an important reference work for all those interested in understanding where law and aging are headed, and for those concerned about the future legal rights of older persons.
T. Carney: Guardianship, "Social" Citizenship, & Theorizing Substitute Decisionmaking Law -- N. A. Kohn: A Civil Rights Approach to Elder Law -- C. P. Sabatino, E. Wood: The Conceptualization of Legal Capacity of Older Persons in Western law -- H. Meenan: Age Discrimination and the Future Development of Elder Rights in the European Union: Walking Side by Side or Hand in Hand? -- A. M. Soden: Family Matters - Some Emerging Legal Issues in Intergenerational and Generational Relations -- I. Doron, B. Spanier: International Elder Law - The Future of Elder Law -- A. Evrard, C. Lacour: A European Approach to Developing the Field of Law and Ageing -- J. Herring: Elder Abuse - A Human Rights Agenda for the Future -- A. Murphy: Aid in Dying - United States and Around the World.
Keywords: Law; Aging -- Research; Demography; Law; Private International Law, International & Foreign Law, Comparative Law; Human Rights; Aging; Demography